Mitofusin2 Promotes β Cell Maturation from Mouse Embryonic Stem Cells via Sirt3/Idh2 Activation - Li Lu; Li Zhitao; Cui Nannan; Huang Mingzhu; Hu Xiaoping; Hong Dongsheng; Pan Zongfu; Lu Xiaoyang (Stem Cells International)
β cell dysfunction is the leading cause of diabetes. Adult β cells have matured glucose-stimulated insulin secretion (GSIS), whereas fetal and neonatal β cells are insensitive to glucose and are functionally immature. However, how β cells mature and acquire robust GSIS is not fully understood. Here, we explored the potential regulatory proteins of β cell maturation process and the capacity for GSIS. Combined with the data from public databases, we found that the gene expression of Mitofusin2 (Mfn2) showed an increasing trend from mouse neonatal β cells to mature β cells. Moreover, its protein expression increased during mouse embryonic pancreas development and β cell differentiation from mouse embryonic stem cells. Knocking down Mfn2 reduced Urocortin3 (Ucn3) expression, GSIS, and ATP production in induced β cells, while overexpressing it had the opposite effect. However, neither Mfn2 knockdown nor overexpression affected the differentiation rate of insulin-positive cells. In immature and mature β cells, Mfn2 and its correlated genes were enriched in tricarboxylic acid (TCA) cycle-related pathways. The expressions of Sirtuin 3 (Sirt3) and isocitrate dehydrogenase 2 (NADP+) and mitochondrial (Idh2) were Mfn2-regulated during β cell differentiation. Inhibiting Idh2 or Sirt3 reduced cellular ATP content and insulin secretion levels that increased by Mfn2 overexpression. Thus, Mfn2 modulated the induced β cell GSIS by influencing the TCA cycle through Sirt3/Idh2 activation. We demonstrated that Mfn2 promoted embryonic stem cell-derived β cell maturation via the Sirt3/Idh2 pathway, providing new insights into β cell development. Our data contribute to understanding diabetes pathogenesis and offer potential new targets for β cell regeneration therapies.